Fimbrial ghf Gene Cluster of Genital Strains of Haemophilus spp. - Bruant, Guillaume (American Society for Microbiology, 2002)
We analyzed the LKP fimbrial gene clusters of six piliated strains of a cryptic genospecies of Haemophilus isolated from the genital tracts of adult patients (five strains) and from an infected neonate. In a group of 19 genital strains, LKP-like genes have been found in only these 6 strains. In addition to the ghfA, ghfD, and ghfE genes previously described, we characterized two genes, designated ghfB and ghfC, encoding the putative chaperone and assembly platform proteins. All six strains had a complete and unique LKP-like gene cluster consisting of the five genes ghfA to ghfE, homologous to genes hifA to hifE of Haemophilus influenzae. The sequences of the coding and intergenic regions of the ghf clusters of the six strains were remarkably homologous. Unlike hif clusters, which are inserted between purE and pepN, the ghf cluster was inserted between purK and pepN on the chromosome. Analysis of the flanking regions of the ghf cluster identified a large deletion, identical in the 5′ end regions of all strains, including the whole purE gene and much of the purK gene. Ultrastructural observations, an attempt at enriching LKP fimbriae, and hemagglutination experiments demonstrated that none of the strains had LKP-type fimbriae. Nevertheless, reverse transcription (RT)-PCR showed that ghf genes were transcribed in four of the six strains. Sequencing of the intergenic ghfA-ghfB regions, including the ghf gene promoters, showed that the absence of transcripts in the remaining two strains was due to a decrease in the number of TA repeats (4 or 9 repeats rather than 10) between the −10 and −35 boxes of the two overlapping and divergent promoters. The other four strains, which had ghf transcripts, had the optimal 10 TA repeats (one strain) or 5 repeats associated with putative alternative −35 boxes (three strains). The absence of 10 repeated palindromic sequences of 44 or 45 nucleotides upstream of ghfB induces an increased instability of mRNA, as quantified by real-time RT-PCR, and may explain why the LKP fimbrial gene cluster is not expressed in these strains.